Business Plan of “Me and Wood” Company in Producing Wood WasteProducts - Oxi Yondi Luci (Soegijapranata Catholic University, 2020)
This research aims at composing a business plan for “Me and Wood” Company in producing wood waste key chain in order to compete in merchandise market,which is reviewed from the aspects of marketing, human resources, operation, and finance. This research gives insight about business plan and business feasibility test and becomes a reference for especially business feasibility study in similar area. Business opportunity of “Me and Wood” was identified with a survey conducted to 58 respondents and observation to manufacturers of similar products. Product marketing is planned to use online media such as website, social media, and e-marketplace. Through innovative planning, the business is expected to develop and has an efficient production process. “Me and Wood” is planned to be located in Kaliwungu, Kendal, Central Java. Human resources involved have specification, job description, detailed organizational structure, and skill. From the calculation results, Payback Period for “Me and Wood” Merchandise Company can be achieved in 2 years and 2 months period, NPV equals to 343,441,899, IRR equals to 49.06% which is higher than the interest rate, and PI equals to 7.06%. If the condition matches the research estimation, then “Me and Wood” merchandise company is feasible.